Gambaran Peresepan Pasien Sirosis Hati di Instalasi Rawat Jalan Rumah Sakit Panti Waluyo Surakarta - Sulistyoningrum, Endah; Murtisiwi, Lusia (Jurnal Farmasi (Journal of Pharmacy), 2020)
Liver cirrhosis is a pathological condition that describes the end-stage progressive hepatic fibrosis characterized by distortion of the liver architecture and the formation of regenerative nodules. Based on the DIY healthprofile in 2008, liver cirrhosis was among the top ten causes of death in DIY Province with a prevalence 0f 1,87% in the ninth place. The purpose of this study was to determine the picture of prescribing liver cirrhosis patients in the Outpatient Installation of Panti Waluyo Hospital. This research is a descriptive study conducted retrospectively. The sample in this study was a saturated sample, that is all members of the population medical record data of patients diagnosed with liver cirrhosis in the Outpatient Installation of Panti Waluyo Hospital, used as a sample with due regard to the inclusion and exclusion criteria, namely liver cirrhosis patients from internal polyclinics with or without complications, have clear,complete data and the medical record data at least contains data on name, age, gender, diagnosis, therapy and without complications of HIV and Oncology, as many as 61 sheets of medical records. Based on the results of research during 2019 it was found that male patients were 55,74% and women 44,26%. Complicating comorbidities in liver cirrhosis patients were ascites 39,34%, portal hypertension 19,67%, esophageal varices 11,48%, liver encephalopathy 3,28%. Patients received single drug therapy namely propranolol and spironolactone as much as 1,64%, and received the most combinations of 2 drug combinations, namely propranolol-curcuma as much as 19,67%, and received a combination of more than 2 drugs at most, namely propranolol-spironolactone-curcuma as much as 11,47%